Software Engineering for Resilient Systems 5th International Workshop, SERENE 2013, Kiev, Ukraine, October 3-4, 2013, Proceedings - Gorbenko, Anatoliy; Romanovsky, Alexander; Kharchenko, Vyacheslav (Programming and Software Engineering, 2013)
This book constitutes the refereed proceedings of the 5th International Workshop on Software Engineering for Resilient Systems, SERENE 2013, held in Kiev, Ukraine, in October 2013. The 13 revised full papers were carefully reviewed and selected from 21 submissions. The papers are organized in topical sections on resilient software and design, rigorous reasoning, applications, concepts, and analysis.